Systematic review of major osteoporotic fracture to hip fracture incidence rate ratios worldwide: implications for Fracture Risk Assessment Tool (FRAX)‐derived estimates. (31st July 2021) - Chakhtoura, Marlene; Dagher, Hiba; Sharara, Sima; Ajjour, Sara; Chamoun, Nariman; Cauley, Jane; Mahfoud, Ziyad; Boudreau, Robert; El Hajj Fuleihan, Ghada
ABSTRACT: The Fracture Risk Assessment Tool (FRAX) is the most widely used tool for fracture prediction. It provides 10‐year probabilities for hip and major osteoporotic fracture (MOF). It uses country‐specific hip fracture incidence and life expectancy data, and for most countries, MOF/hip fracture incidence rate ratios (IRRs) from Malmo Sweden. However, the risk of MOF varies by age, sex, and geography. The objective is to compare the MOF/hip IRRs across countries, by sex and age. This systematic review targeted observational studies of MOF and hip fractures in individuals >50 years (PROSPERO 2019 CRD42019129259). One reviewer screened potential articles. Two reviewers completed duplicate and independent data abstraction, and assessed study quality based on population representativeness, study design and duration, definition of ethnicity, and fracture characteristics. We calculated the MOF/hip IRRs (95% confidence interval) and Z ‐values to compare IRRs in various countries to those for Sweden. We included 27 studies, of fair to good quality in the majority, from Europe (15), US and Canada (7), Asia (3), and Australia (2). The IRRs were twofold to 10‐fold higher in younger compared to older age categories, and in women compared to men, with few exceptions. Within Europe, and using Sweden as a reference, MOF/Hip IRRs in women 50–54 years from Finland, Italy, Netherlands, Denmark, and UK were significantly lower by 38% to 60%. Findings were similar in men. At older ages, MOF/Hip IRRs were consistently lower in women from European countries compared to Sweden, by 10%–40% and 11%–51%, at 75–79 years and 85–89 years, respectively. Findings were heterogenous in men and in non‐European countries. In conclusion, the MOF/hip fracture IRR may vary between countries. The variability at older ages may affect FRAX prediction when country‐specific fracture IRRs are not used. Further research is needed to elucidate the implication of our findings to FRAX‐derived MOF estimates in various countries. © 2021 American Society for Bone and Mineral Research (ASBMR).